On Effects of Stochastic Volatility and Long Memory Towards Mortgage Insurance Models: An Empirical Study - Alhagyan, Mohammed; Misiran, Masnita; Omar, Zurni (Pushpa Publishing House, Prayagraj, India, 2021)
The change in collateral price is one of the challenges in modeling mortgage insurance. Current work mostly considers collateral price similar to addressing risky asset modelling, in which geometric Brownian motion is being used to model its underlying processes. This assumption has been heavily criticized due to its lack of fundamental dependencies in its distribution. This work provides